2014
DOI: 10.1111/cdoe.12095
|View full text |Cite
|
Sign up to set email alerts
|

Associations of number of teeth with risks for all‐cause mortality and cause‐specific mortality in middle‐aged and elderly men in the northern part of Japan: the Iwate‐KENCO study

Abstract: The number of teeth is an important predictive factor for mortality among middle-aged Japanese men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 33 publications
5
42
0
Order By: Relevance
“…To the best of our knowledge, the current study, with over 170 000 participants, is larger than any previous prospective study of oral health and CVD,13 15 16 and is the only one that looks at the association between severity of oral health problems and the risk of a range of non-fatal CVD outcomes and all-cause mortality within the same cohort. Previous epidemiologic studies varied in the oral health exposures (periodontitis (self-reported, clinical or radiographic), gingivitis, tooth loss classification, bone loss, pocket depth) and in the definition of CVD outcomes;3 13 28–30 therefore, the associations have not been consistently replicated.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…To the best of our knowledge, the current study, with over 170 000 participants, is larger than any previous prospective study of oral health and CVD,13 15 16 and is the only one that looks at the association between severity of oral health problems and the risk of a range of non-fatal CVD outcomes and all-cause mortality within the same cohort. Previous epidemiologic studies varied in the oral health exposures (periodontitis (self-reported, clinical or radiographic), gingivitis, tooth loss classification, bone loss, pocket depth) and in the definition of CVD outcomes;3 13 28–30 therefore, the associations have not been consistently replicated.…”
Section: Resultsmentioning
confidence: 97%
“…13–15 17 28 The Iwate-KENCO study,15 among men aged 40–79 years free from CVD at baseline, which used similar measures of tooth loss, reported higher risk of all-cause mortality in those with none of their natural teeth left, compared with those reporting ≥20 natural teeth left (HR 1.46 (1.12 to 1.91) when adjusted for age and 1.28 (0.97 to 1.68) when multivariate adjusted). The Scottish cohort study4 of over 12 000 people with linked mortality showed increased risk of all-cause mortality and CVD mortality (HRs 1.30 (1.12 to 1.50) and 1.49 (1.16 to 1.92), respectively) among those with none of their natural teeth left compared with participants with natural teeth only.…”
Section: Resultsmentioning
confidence: 99%
“…Five cohort studies were eventually included in the meta‐analysis 7,16,17,19,26 . Reasons for exclusion of the seven excluded studies were: 1) lack of data (n = 3); 27–29 2) inappropriate study design (case‐control study, n = 1; intervention study, n = 1); 11 , 30 and 3) inappropriate exposure (tooth loss; n = 2) 8 , 18 Figure 1. illustrates the study selection process.…”
Section: Resultsmentioning
confidence: 99%
“…Edentulous rates are a crucial indicator of the operation of a country's oral healthcare system; therefore, it is imperative to monitor its occurrence . Several studies have shown that tooth loss is a predictor of cardiovascular mortality and could be a useful risk indicator for atherosclerosis …”
Section: Introductionmentioning
confidence: 99%
“…11 Edentulous rates are a crucial indicator of the operation of a country's oral healthcare system; therefore, it is imperative to monitor its occurrence. 12 Several studies have shown that tooth loss is a predictor of cardiovascular mortality [13][14][15][16] and could be a useful risk indicator for atherosclerosis. 17 Epidemiological studies in the dental and medical area have supported the potential association between increased blood pressure, hypertension, and periodontitis through the inflammation pathway.…”
Section: Introductionmentioning
confidence: 99%